Are children with higher self-reported wellbeing and perceived motor competence more physically active? A longitudinal study. Issue 3 (March 2020) - Visser, Ebonee L.; Mazzoli, Emiliano; Hinkley, Trina; Lander, Natalie J.; Utesch, Till; Barnett, Lisa M.
Abstract: Objectives: Self-perceptions such as perceived motor competence and psychosocial wellbeing have been identified as important to children's physical activity. The study's purpose was to explore whether perceived motor competence and psychosocial wellbeing were determinants of physical activity, one year after a baseline assessment. Design: Longitudinal study. Methods: A total of 134 children (65.7% boys, 34.3% girls) aged 6–7 years at baseline (2016), and 7–8 years at follow-up (2017) were included in this study. Pearson's correlations assessed associations at baseline and follow-up between moderate- to vigorous-intensity physical activity (MVPA) (accelerometers) and (i) total perceived motor competence and subdomains (the pictorial scale of Perceived Movement Skill Competence) and (ii) psychosocial wellbeing and sub-domains — KidKINDL KINDer Lebensqualitätsfragebogen: Children Quality of Life Questionnaire (KINDL R ). Variables identified as significant in Pearson's correlations were included in mixed model analyses, adjusting for accelerometer wear time, sex and age. Results: Baseline perceived object control skills was associated with MVPA at follow-up (r = 0.38, p < 0.001), but perceived locomotor skills were not. Self-esteem was the only subdomain of psychosocial wellbeing that demonstrated significant association with MVPA at baseline (r = 0.21, p < 0.05). Perceived object control (B = 1.36, p = 0.019, 95% CI [0.23, 2.50]) and self-esteem (B = 0.32, p = 0.001, 95% CI [0.13, 0.50]) positively predicted MVPA; albeit with small effects. Conclusions: Focusing on improving children's perceived object control and self-reported self-esteem may contribute to children's physical activity participation.